The Influence of Production and Destruction of O Isotopes in Red Giant Stars - Selman, Ahmed Abdul-Razzaq (Iraqi Journal of Science, 2023)
Thermonuclear reaction rates are calculated for three oxygen isotopes 14,15,16O in CNO cycles reactions occurring in red giant stars. These reactions are:, , , , and . Reaction rates have been calculated using Matlab codes, and related comparisons were made with NACRE II and Reaclib libraries, and the ratios of production to the destruction of 15,16O isotopes were found. Present reaction rate results were close to most of the selected reactions, and in some cases larger with a factor of 1-3. 15,16O production to destruction ratios indicated a special tendency to saturate at temperatures higher than ~ 2 GK, and these ratios were in general larger than 1 indicating an excess of producing such isotopes in red giant stars.